Evaluasi Penerapan Layanan Tiket Kereta Api On-Line - Kuswati, Atik S (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
The on line booking system is one of the breakthrough to impraue seroice to customer. The implementation of on line ticketing strategy has been both exciting and challenging. This study intends to evaluate the implementation of railway on line ticketing system. The methods of analysis use descriptive analysis and cross tabulation. This method will obtain a data description related to the evaluation of on line train ticket sales after implementing this regulation. There are 81.82 % of respondents that bought a train ticket by coming in the railway station, The age respondents between 25 to 34 years knew about this system as much as 31.8%. A total of 14.4% of respondents is ever buy ticket by that system and 56.8% of total respondent are know well how to buy ticketing by on line but they never do that way. From the Pearson chisquare of the probability value can be obtained a description of the relationship between education respondents with knowledge of on line ticketing, relationship between on line ticketing and a have or have not purchased tickets on line, as well as the relationship between respondents opinions about the on line ticketing system with a successfal application.Keywords: train ticket, on line seroices Penjualan tiket secara on line merupakan salah satu terobosan guna meningkatkan layanan kepada pelanggan. Pelaksanaan sistem on line ini cukup menarik dan banyak tantangan. Penelitian ini bermaksud mengevaluasi penerapan sistem layanan tiket kereta api secara on line. Metode yang digunakan adalah analisis deskriptif serta cross tabulation atau disebut juga tabulasi silang. Melalui metode ini diperoleh gambaran/ deskripsi data terkait dengan evaluasi penerapan sistem on line penjualan tiket kereta api, yaitu sebanyak 81,82% responden membeli tiket kereta api dengan datang ke stasiun, responden yang berusia 25 s.d 34 tahun sebanyak 31.8% mengetahui tentang on line ticketing. Sebanyak 14.4 % responden mengetahui tentang on line ticketing pemah membeli secara on line., tetapi sebanyak 56.8% walaupun sudah mengetahui tentang on line ticketing tetapi belum pemah membeli secara on line. Dari nilai probabilitas untuk pearson chi-square diperoleh gambaran adanya hubungan antara pendidikan responden dengan pengetahuan tentang on line ticketing, hubungan antara mengetahui on line ticketing dengan pemah a tau belum membeli tiket secara on line, serta hubungan antara pendapat responden tentang sistem on line ticketing dengan keberhasilan penerapannya.Kata kunci: tiket kereta api, pelayanan on line.